KLRC1 knockout overcomes HLA-E-mediated inhibition and improves NK cell antitumor activity against solid tumors - Mac Donald, Alice; Guipouy, Delphine; Lemieux, William; Harvey, Mario; Bordeleau, Louis-Jean; Guay, David; Roméro, Hugo; Li, Yuanyi; Dion, Renaud; Béland, Kathie; Haddad, Elie (Frontiers in Immunology, 2023)
NK cells hold the potential to shift cell therapy from a complex autologous option to a universal off-the-shelf one. Although NK cells have demonstrated efficacy and safety in the treatment of leukemia, the limited efficacy of NK-cell-based immunotherapies against solid tumor still represents a major hurdle. In the immunosuppressive tumor microenvironment (TME), inhibitory interactions between cancer and immune cells impair antitumoral immunity. The KLRC1 gene encodes the NK cell inhibitory receptor NKG2A, which is a potent NK cell immune checkpoint. NKG2A specifically binds HLA-E, a non-classical HLA class I molecule frequently overexpressed in tumors, leading to the transmission of inhibitory signals that strongly impair NK cell function.To restore NK cell cytotoxicity against HLA-E + tumors, we have targeted the NKG2A/HLA-E immune checkpoint, by using a CRISPR-mediated KLRC1 gene editing. KLRC1 knockout resulted in a reduction of 81% of NKG2A + cells frequency in ex vivo expanded human NK cells post-cell sorting. In vitro, the overexpression of HLA-E by tumors cells significantly inhibited WT NK cell cytotoxicity with p-values ranging from 0.0071 to 0.0473 depending on tumor cell lines. In contrast, KLRC1 KO NK cells exhibited significantly higher cytotoxicity compared to WT NK cells against 4 different HLA-E + solid tumor cell lines, with p-values ranging from <0.0001 to 0.0154. Interestingly, a proportion of 43.5 to 60.2% of NKG2A -NK cells within the amplified NK cell population was sufficient to reverse at its maximum the HLA-E mediated inhibition of NK cell cytotoxicity. The expression of the activating receptor NKG2C was increased in KLRC1 KO NK cells and contributed to the improved NK cell cytotoxicity against HLA-E + tumors. In vivo, the adoptive transfer of human KLRC1 KO NK cells significantly delayed tumor progression and increased survival in a xenogeneic mouse model of HLA-E + metastatic breast cancer, as compared to WT NK cells (p=0.0015). Our results demonstrate that KLRC1 knockout is an effective strategy to improve NK cell antitumor activity against HLA-E + tumors and could be applied in the development of NK-cell therapy for solid tumor.